The Analysis of the Influence of Card-Based Payment and Electronic Money on Money Supply - Adhinda Rachma Aminy (Journal of Contemporary Information Technology, Management, and Accounting, 2022)
The development of technology has changed many areas of people's lives, one of which is in the transaction process. Non-cash payment instruments such as non-cash payment instruments and electronic money are increasingly being used by the community. This increase affects the money supply. Through multiple linear regression tests, this study aims to see the influence of card-based payments and electronic money on the money supply. The data taken is the nominal credit card, debit card, electronic money as the independent variable, and the money supply as the dependent variable. The data taken is only limited to the period from January 2016 to April 2020. The results of the analysis show that debit cards and electronic money have a significant positive effect on the money supply, while credit cards have a significant negative effect on the money supply.